Vulnerability and Climate Change - Farhana Zaman; Rowshan Ara; Fazlul Karim (Bangladesh Journal of Bioethics)
Climate change has emerged as a significant threat to global development, disproportionately affecting vulnerable populations, particularly in developing countries like Bangladesh. This paper explores the complex relationships between climate change and vulnerability, highlighting how geographical exposure, socioeconomic conditions, and gender disparities increase the susceptibility to climate-induced hazards such as floods, cyclones, and salinity intrusion.  Vulnerability is not steadfast in the environmental factors, but it is deeply influenced by poverty, limited access to resources, and systematic inequalities. Discussion emphasizes the gender nature of vulnerability, with women facing additional barriers to adaptation due to traditional roles and social constraints. Institutional policy responses are viewed, underscoring the need for inclusive governance, education, and long-term financial support. The study recommends a holistic and equity-focused approach to climate adaptation that prioritizes empowerment, gender inclusion, and localized solutions. Strengthening institutional capacity, increasing climate finance, and integrating climate into education and policy frameworks are vital to sustainable adaptation.